Investigation of full heavy $$QQQQ'\bar{Q}$$ Q Q Q Q ′ Q ¯ pentaquark candidates - K. Azizi; Y. Sarac; H. Sundu (European Physical Journal C: Particles and Fields)
Abstract Recent breakthroughs in research and experimentation have led to the identification of numerous exotic states in particle physics. Each new discovery not only sparks excitement for future findings but also fuels interest in uncovering additional unknown states. Motivated by this perspective and the recent identification of both standard and exotic hadrons with an increasing number of heavy quarks, this study conducts a spectroscopic analysis of possible pentaquark candidates with spin-parity $$\frac{1}{2}^-,$$ 1 2 - , and quark content of $$cccb\bar{c}$$ c c c b c ¯ and $$bbbc\bar{b}.$$ b b b c b ¯ . The masses of these states are calculated by considering the relevant Lorentz structures, including and $${\mathbbm {1}},$$ 1 , yielding the following results, respectively: for the $$P_{(4cb)}$$ P ( 4 c b ) state, $$m_{P_{(4cb)}} = 11388.30 ± 107.79$$ m P ( 4 c b ) = 11388.30 ± 107.79 MeV and $$m_{P_{(4cb)}} = 11368.30 ± 112.68$$ m P ( 4 c b ) = 11368.30 ± 112.68 MeV, and for the $$P_{(4bc)}$$ P ( 4 b c ) state, $$m_{P_{(4bc)}} = 20998.30 ± 121.52$$ m P ( 4 b c ) = 20998.30 ± 121.52 MeV and $$m_{P_{(4bc)}} = 20990.50 ± 125.87$$ m P ( 4 b c ) = 20990.50 ± 125.87 MeV. Additionally, the current coupling constants of these states to the vacuum, which are essential for analyzing their potential decay modes, are also provided in this study.